The Sociology Book: Big Ideas Simply Explained - Sarah Tomley (DK, 2015)
The Sociology Book takes on some of humankind's biggest questions: What is society? What makes it tick? Why do we interact in the way that we do with our friends, coworkers, and rivals? The Sociology Book profiles the world's most renowned sociologists and more than 100 of their biggest ideas, including issues of equality, diversity, identity, and human rights; the effects of globalization; the role of institutions; and the rise of urban living in modern society